RESPON AMERIKA SERIKAT PADA MASA PEMERINTAHAN PRESIDEN DONALD TRUMP TERHADAP PROGRAM NUKLIR KOREA UTARA - Geno Vybra Yoga (UIR Press, 2020)
This research aims to explain the application of the United states deterrence strategy in response to the development of North Korea's nuclear program during the administration of Donald Trump in 2017-2019. As a super power country, he has a responsibility to create and maintain security stability in the world. This research use deterrence as theory. According to Silvia Romeo, the deterrence strategy includes three activities namely persuading the target country to cancel its intention; take action against the target country; and policy changes through changes in government. Qualitative methods applied in this research. The result is that the United States carried out a deterrence strategy against North Korea related to the development of its nuclear program through several measures such as the imposition of economic sanctions, strengthening the defense sector with its allies, South Korea and Japan by reforming the defense cooperation alliance and installing the THAAD defense system in South Korea, and negotiations through the Singapore Summit in 2018 and the Vietnam Summit in 2019. The purpose of this is to realize the denuclearization of North Korea and also as a form of US efforts to maintain its hegemony in the Asia Pacific region.